Perencanaan dan Peningkatan Kinerja Organisasi - Alfian Ihsan Ramadani; Ahmad Hafid Kafi Zakariya; Seny Alfina Amalia Amanda; Holifatul Hasanah; Nurul Hikmah; Mu'alimin Mu'alimin (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Improving organizational performance is a crucial issue in the era of increasingly dynamic and competitive globalization. This study aims to explore the role of management psychology in improving organizational performance, focusing on factors such as motivation, group dynamics, and organizational culture. The research method used is a literature review, by collecting and analyzing data from various sources such as books, journals, and scientific articles. The results of the study indicate that strategic planning, human resource development, and the application of information technology are important factors in improving organizational performance. In addition, a positive organizational culture and effective leadership also contribute significantly to improving performance. This study fills the literature gap by emphasizing the importance of psychological aspects in performance management, which are often overlooked in previous studies.